Mapping modifiable determinants of medication adherence in bipolar disorder (BD) to the theoretical domains framework (TDF): a systematic review. Issue 7 (19th May 2021) - Prajapati, Asta Ratna; Dima, Alexandra; Mosa, George; Scott, Sion; Song, Fujian; Wilson, Jonathan; Bhattacharya, Debi
Abstract: Background: Around 40% of people with bipolar disorder (BD) are non-adherent to medication leading to relapse, hospitalisation and increased suicide risk. Limited progress in addressing non-adherence may be partly attributable to insufficient understanding of the modifiable determinants of adherence that require targeting in interventions. We synthesised the modifiable determinants of adherence in BD and map them to the theoretical domains framework (TDF). Method: We searched CINAHL, Cochrane Library, Embase, LILACS, Medline, PsychINFO and PubMed until February 2020. We included studies reporting modifiable determinants of adherence in BD. Two reviewers independently screened studies, assessed quality, extracted modifiable determinants and mapped them to TDF. Results: We included 57 studies involving 32 894 participants. Determinants reported by patients spanned 11 of the 14 TDF domains compared to six domains represented by clinician/researcher. The TDF domains most commonly represented (% and example) in studies were: 'Environmental context and resources' (63%, e.g. experiencing side effects), 'Beliefs about consequences' (63%, e.g. beliefs about medication effects), 'Knowledge' (40%, e.g. knowledge about disorder), 'Social influences' (33%, e.g. support from family/clinicians), 'Memory, attention and decision processes' (33%, e.g. forgetfulness), 'Emotion' (21%, e.g. fear of addiction) and 'Intentions' (21%, e.g. wanting alternative treatment). 'Intentions', 'Memory, attention and decision processes' and 'Emotion' domains were only reported by patients but not clinicians. Conclusions: Clinicians may be underappreciating the full range of modifiable determinants of adherence and thus not providing adherence support reflective of patients' needs. Reporting of modifiable determinants in behavioural terms facilitates developing theory-based interventions to address non-adherence in BD.